Efeitos osteogênicos in vitro e in silico de dois triterpenos semi-sintéticos derivados de Combretum leprosum: possíveis mecanismos de ação - Nogueira Júnior, Valdo (2022)
Bonetissueis a specializedformofextremelyorganizedconnectivetissueandoneofthemostadaptable in thehuman body. Among its cells, osteoblastsact in tissuereplacement, beingpartoftheprocesscalledboneremodeling. Withadvancingage, the balance betweenreabsorption and neoformationisaltered, causing a decrease in bonestrength and density. In thisperspective, thepresentstudyaimedtoinvestigatethecompounds CL-P2 and CL-P2a (derivedfromtheplantCombretumleprosum) in theproliferation, activation and mechanismofaction in murine osteoblasts in vitro. Cell viability and proliferationwereevaluatedby MTT assay and immunostainingwith Ki67, respectively, after 24, 48 and 72 hoursofincubationofosteoblastswithcompounds CL-P2 and CL-P2a. Differentconcentrationsofbothsubstanceswereusedfor MTT (2.5μM, 5μM, 10μM and 20μM), and fromtheresultsobtained, a concentrationofeachcompound (CL-P2 (2.5μM) and CL-P2a (10μM)) wereselectedforfurtherassays: immunostainingwith Ki67, quantificationofbonealkalinephosphatase (FAO) levels in the culture medium after 24, 48 and 72 hours , 5, 7, 14 and 21, toconfirmtheboneactivitybythecells, weperformedthemineralizationassaybyVonKossastain, after 7, 14 and 21 daysofcell culture. Toinvestigatethemechanismsinvolved in cellactivation, theproteinexpressionsof BMP-2, OPG and RANK-L wereinvestigatedbyimmunostaining and WesternBlot (WB) and comparedwiththeinteractionsprovided in the molecular dockingstudy. A significantincrease in osteoblastviabilitywasobserved after incubationofcellswith CL-P2 and CL-P2a compoundsfor 24, 48 and 72h, as well as animportantincrease in cellproliferation at CL-P2 doses (2.5 μM) and CL-P2a (10μM) in a 24h period. In theassayfor FAO dosage in the culture medium, a significantincrease in FAO wasobserved after CL-P2 (2.5μM) and CL-P2a (10μM) incubation after 48 hours, keepingitifincreased up to 21 daysof trial. In theVonKossaassay, anincrease and accelerationofmineralizationwereobserved in theconcentrationsof CL-P2 (2.5μM) and CL-P2a (10μM), at 14 and 21 days. In immunostaining and WB assays, therewasanincrease in theexpressionof BMP2, RANK-L and OPG, characterizingtheactivationofthebonepathway, in theinvestigationofthe WNT, β-catenin, DKK pathway, therewasanincrease in theproteinexpressionof WNT (CL- P2 2.5M) and β-catenin (CL-P2 2.5μM/ CL-P2a 10μM), do not alter theexpressionof DKK. Theresultssuggest a positive effectofthecompounds CL-P2 and CL-P2a, in thebestcontractionsof 2.5μM and 10μM, respectively, ontheproliferation, viability and activationofosteoblasts. Thus, promisingstudies can be carriedoutwiththecompounds CL-P2 and CL-P2a withtheir use in bonemetabolismpathways.